MEKANISME PENGISIAN JABATAN ASN DARI ANGGOTA PRAJURIT TNI / POLRI DALAM UU ASN NO 20 TAHUN 2023 DITINJAU DARI MASLAHAH MURSALAH - sekarwati, henny (TAQNIN: Jurnal Syariah dan Hukum, 2025)
The enactment of Law Number 20 of 2023 on the State Civil Apparatus (ASN) provides an opportunity for active TNI/POLRI personnel to occupy certain ASN positions, raising concerns regarding bureaucratic neutrality and the merit-based system in national employment. This study aims to analyze the process of filling ASN positions by TNI/POLRI personnel based on the ASN Law of 2023 and evaluate it from the perspective of Maslahah Mursalah in Islamic law.The research method employed is a normative juridical study with a legislative approach. The analysis is conducted qualitatively and descriptively by examining relevant regulations and the principles of Maslahah Mursalah in Islamic law. The findings indicate that this policy has the potential to weaken the merit system, blur the distinction between military institutions and civil bureaucracy, and create opportunities for conflicts of interest and abuse of power. From the perspective of Maslahah Mursalah, this policy can be classified as a primary benefit (maslahat daruriyyat) if it positively impacts bureaucratic stability and national resilience. However, if it leads to injustice in the ASN promotion system and undermines bureaucratic neutrality, it is more likely to result in harm rather than benefit.Keywords: ASN, TNI/POLRI, merit system, Maslahah Mursalah, bureaucratic neutrality.